2015
DOI: 10.1186/s12883-015-0508-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese version of the FOUR score in the assessment of neurosurgical patients with different level of consciousness

Abstract: BackgroundThe Glasgow Coma Scale (GCS) is currently the most widely used scoring system for comatose patients. A decade ago, the Full Outline of Unresponsiveness (FOUR) score was devised to better capture four functional aspects of consciousness (eye, motor responses, brainstem reflexes, and respiration). This study aimed to validate the Chinese version of the FOUR score in patients with different levels of consciousness.MethodsThe study had two phases: (1) translation of the FOUR score, and (2) assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 28 publications
6
23
0
8
Order By: Relevance
“…In this study, where GCS and FOUR scores have been compared in brain tumor or head trauma patients at the intensive care unit, we found that the FOUR score is as effective and trustworthy as GCS. Other reports also reveal the same thing as our study (1,4,(7)(8)(9)13).…”
Section: █ Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, where GCS and FOUR scores have been compared in brain tumor or head trauma patients at the intensive care unit, we found that the FOUR score is as effective and trustworthy as GCS. Other reports also reveal the same thing as our study (1,4,(7)(8)(9)13).…”
Section: █ Discussionsupporting
confidence: 92%
“…Also correlation for both scales was quite strong. Other studies have stated that coefficient of concordance and correlation between practitioners were high as in our work (5,7,9,10,(12)(13)(14). This conclusion is thought to be helpful for decreasing mistakes when evaluating intensive care unit patients and a more accurate evaluation can be made.…”
Section: █ Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The etiology of secretory otitis media in adults is complex and related to many factors [5]. Laryngopharyngeal reflux disease (LPRD), pharyngitis, sinusitis, and respiratory dysfunction are common predisposing factors [6][7][8]. Animal models have confirmed that gastric contents can cause inflammation in the throat and nasal cavity, and can reach the tympanum through the eustachian tube [9].…”
Section: Introductionmentioning
confidence: 99%